Strengthening Community Organizations through Social Service (Building Synergy and Participation in Bintan Urban Village) - Dede Mirza; Lili Suryani; Seroja Indah Lestari; Sutrisno Sutrisno (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
Community participation in social service activities is a crucial indicator of community-based social development. However, the level of participation is often influenced by various structural and cultural factors, including the role of community organizations as key mobilizers of collective action. This activity aims to identify factors affecting community participation in social service activities in Bintan Sub-district, analyze the role of community organizations in facilitating and organizing these activities, and assess their impact on strengthening synergy and collaboration among residents. The method employed included a socialization session on the importance of community organizations in community empowerment, followed by social service activities in the form of collective environmental clean-up and greening programs through tree planting around public facilities. The findings indicate that increased collective awareness, local leadership, and organizational support significantly enhance community participation. Furthermore, social service activities contribute to strengthening social cohesion, fostering a sense of togetherness, and promoting stronger synergy and collaboration among community members in Bintan Sub-district.